(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2026)
This study aimed to assess the effectiveness of a training program based on artificial intelligence tools in enhancing educational film production skills among pre-service teachers majoring in Kindergarten Education. A quasi-experimental design with descriptive components was employed. The sample included 64 fourth year female students from the College of Education at Kuwait University, divided into a control group (n = 33) and an experimental group (n = 31). The experimental group received a structured AI based training program comprising five sessions (two hours each), using tools such as ChatGPT 4, MagicLight.AI, and Focal.AI. To measure the impact, the researcher developed and validated three instruments: the Educational Film Production Skills Scale, an Observation Checklist, and an Educational Film Quality Evaluation Form. The findings revealed statistically significant differences in post test scores in favor of the experimental group, indicating a marked improvement in their film production skills. Observation results rated their performance as “excellent,” and the final films produced demonstrated high quality according to pedagogical, technical, and linguistic standards. The effect size was large, confirming the training program’s substantial impact on students’ practical competencies in digital educational media production. Based on these findings, the study recommends adopting and generalizing this training model in kindergarten teacher preparation programs, due to its effective role in empowering pre-service teachers to produce interactive digital content that supports language learning among preschool children.